2003
DOI: 10.1261/rna.5420503
|View full text |Cite
|
Sign up to set email alerts
|

The Ref/Aly proteins are dispensable for mRNA export and development in Caenorhabditis elegans

Abstract: The mRNA export pathway is highly conserved throughout evolution. We have used RNA interference (RNAi) to functionally characterize bona fide RNA export factors and components of the exon-exon junction complex (EJC) in Caenorhabditis elegans. RNAi of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
78
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(92 citation statements)
references
References 77 publications
14
78
0
Order By: Relevance
“…This conclusion was further supported by the observation that cells with a knockdown of REF expression had no defect in ORF57-enhanced ORF59 expression. Other studies also show no defect in RNA export in REF knock-out animals (34,51). During the course of our manuscript preparation, Chen et al (52) reported that HSV-1 ICP27, a hom- olog of KSHV ORF57, mediates viral RNA export through the TAP/NXF1 pathway independent of its interaction with REF.…”
Section: Discussionmentioning
confidence: 64%
“…This conclusion was further supported by the observation that cells with a knockdown of REF expression had no defect in ORF57-enhanced ORF59 expression. Other studies also show no defect in RNA export in REF knock-out animals (34,51). During the course of our manuscript preparation, Chen et al (52) reported that HSV-1 ICP27, a hom- olog of KSHV ORF57, mediates viral RNA export through the TAP/NXF1 pathway independent of its interaction with REF.…”
Section: Discussionmentioning
confidence: 64%
“…In contrast, TAP-mediated export of cellular poly(A) + mRNAs involves its indirect recruitment to mRNAs by mRNA export adapter proteins such as Aly/REF (Yra1p in yeast) Stutz et al 2000;Zhou et al 2000;Rodrigues et al 2001). Given that Aly/REF is not essential for mRNA export (Gatfield and Izaurralde 2002;Longman et al 2003) and that other RNA binding proteins have been shown to interact with TAP (Huang et al 2003), it is likely that Aly/REF is only one of a number of adapter proteins for TAP.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it has a role in DNA replication distinct from its role in mRNA export (24). Although Aly directly binds UAP56 and couples it to spliced mRNA, REF/Aly is dispensable for mRNA export in Drosophila (25) and Caenorhabditis elegans (26).…”
mentioning
confidence: 99%